Evaluating the effectiveness of policies against a pandemic - Christian Alemán; Christopher Busch; Alexander Ludwig; Raül Santaeulàlia-Llopis (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
We develop a novel empirical approach to identify the effectiveness of policies against a pandemic. The essence of our approach is the insight that epidemic dynamics are best tracked over stages, rather than over time. We use a normalization procedure that makes the pre-policy paths of the epidemic identical across regions. The procedure uncovers regional variation in the stage of the epidemic at the time of policy implementation. This variation delivers clean identification of the policy effect based on the epidemic path of a leading region that serves as a counterfactual for other regions. We apply our method to evaluate the effectiveness of the nationwide stay-home policy enacted in Spain against the Covid-19 pandemic. We find that the policy saved 15:9% of lives relative to the number of deaths that would have occurred had it not been for the policy intervention. Its effectiveness evolves with the epidemic and is larger when implemented at earlier stages.
Keywords: E01; E22; E25; 330; Macroeconomics; Pandemic; Stages; Covid-19; Stay-Home; Policy Effects; Identification